Epigenome-wide meta-analysis identifies DNA methylation biomarkers associated with diabetic kidney disease - Laura J. Smyth; Emma H. Dahlström; Anna Syreeni; Katie Kerr; Jill Kilner; Ross Doyle; Eoin Brennan; Viji Nair; Damian Fermin; Robert G. Nelson; Helen C. Looker; Christopher Wooster; et al. (Nature Communications, 2022)
Approximately 40 percent of people with type 1 diabetes develop kidney disease, but the risk factors are not well understood. Here, the authors identify DNA methylation signatures associated with diabetic kidney disease, of which 21 biomarkers predict the development of kidney failure.